EMPOWERING STUNTING PREVENTION: INTEGRATIVE AND COLLABORATIVE INITIATIVE BASED ON THE LOCAL WISDOM OF TENGGER TRIBE - Muniroh, Lailatul; Ambarini, Tri Kurniati; Putri, Anggraeny Monica; Oktavia, Shanty; Santosa, Faradyah Lulut; Lailata, Irina (Universitas Airlangga, 2025)
Wonokitri Village is a traditional village for the Tengger Tribe, located in the Tosari District of Pasuruan Regency. The village faces several health issues, including a high prevalence of stunted children (23.8%), 21% of mothers not providing colostrum to infants, and 60% of mothers not exclusively breastfeeding because they have introduce complementary foods before the baby reaches six months old. Other health problems include infants with low birth weight, short birth length, and a high rate of premature birth (66%). Therefore, the goal of community service was to prevent stunting through an integrative and collaborative movement based on local wisdom in Wonokitri Village, involving prospective brides, pregnant women, and parents of toddlers as the main targets. The activities begin with coordination with the Village Head and the Head of Community Empowerment. Subsequent activities include situational analysis, social mapping, Focus Group Discussions (FGD), and in-depth interviews to obtain more detailed information about the local wisdom of the Tengger Tribe. Next,the Community Service Team conducts various educational and training activities to enhance the knowledge and skills of the target. Education was conducted using four modules: The Prevent Stunting in Toddler module targeting mothers of toddlers; Prevent Anemia targeting prospective female brides; Maternal Health targeting pregnant women; and Living Healthy Without Smoking targeting fathers of toddlers. In addition, mentoring and home visits were also conducted for pregnant women with Chronic Calorie Deficiency and stunted toddlers. The results of the activities showed an increase in knowledge levels regarding stunting, the dangers of smoking, anemia prevention, and maternal health before and after the education sessions.